2020
DOI: 10.1186/s12889-020-8406-5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring retention in care for HIV-positive pregnant women in Prevention of Mother-to-Child Transmission of HIV (PMTCT) option B+ programs: the Mozambique experience

Abstract: Background: Failure to retain HIV-positive pregnant women on antiretroviral therapy (ART) leads to increased mortality for the mother and her child. This study evaluated different retention measures for women's engagement along the continuum of care for prevention of mother-to-child transmission (PMTCT) option B+ services in Mozambique. Methods: We compared 'point' retention (patient's presence in care 12-month post-ART initiation or any time thereafter) with the following definitions: alive and in care 12 mon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Study findings on implementation of Option B+ guidelines are similar to previous studies confirming progress on HIV testing and lifelong ART for HIV-infected pregnant and breastfeeding women and persistent gaps in HIV testing for exposed infants 1 , 8 , 21 23 . One factor that may contribute to this gap is the finding that HIV+ women are more likely to be lost to follow up when they were started on ART in compliance with Option B+ guidelines (i.e, they are pregnant) as compared to those who are started on ART in response to physical symptoms 22 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Study findings on implementation of Option B+ guidelines are similar to previous studies confirming progress on HIV testing and lifelong ART for HIV-infected pregnant and breastfeeding women and persistent gaps in HIV testing for exposed infants 1 , 8 , 21 23 . One factor that may contribute to this gap is the finding that HIV+ women are more likely to be lost to follow up when they were started on ART in compliance with Option B+ guidelines (i.e, they are pregnant) as compared to those who are started on ART in response to physical symptoms 22 .…”
Section: Discussionsupporting
confidence: 84%
“…The study also identified salient contextual factors that influenced guideline implementation, many of which align with those identified in other implementation studies in low-resource settings 18 and in other studies of the implementation of Option B+ guidelines, such as periodic shortages of HIV testing kits and ART drugs 19 , 20 . In contrast to this study's focus on support providers and health centre staff, prior research also has identified factors at the community level that affect HIV positive women including lack of transportation, work conflicts, and stigma associated with HIV 20 , 21 . A distinct feature of this study is the focus on contextual factors that influenced not only guideline implementation but also the delivery of support strategies and the finding that transportation challenges played a central role in limiting the delivery of technical assistance to some of the health centres.…”
Section: Discussionmentioning
confidence: 85%
“…However, such mechanisms require rigorous planning, and their effect on the quality of service delivery must be carefully monitored [22]. Other initiatives have been designed to address the failure to retain HIV-positive pregnant women in cART, such as a review of retention (timeliness and regularity of antenatal care visits) in pregnant women at antenatal care services [23].…”
Section: Plos Onementioning
confidence: 99%
“…This makes it challenging to develop interventions to improve engagement or evaluate whether they are having the intended effect [ 5 ]. Strategic decisions can also be made more challenging by inaccurate interpretation of programme successes [ 6 ], misunderstanding the magnitude of the challenge [ 3 ] or inaccurate justification of costs [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%